An ultimatum game with probabilistic role swapping : an experimental analysis - Fu, Yingyu (2015)
The proposers’ and recipients’ behaviors in the ultimatum game can be affected by various factors, such as participation cost, time constraint, stake size, etc. Another possible element can be role swapping which involves the change of dominant/non-dominant positions between two subjects. An experiment conducted by Weg and Smith (1993) suggested that the proposers proposed higher offer when role swapping was involved. However, no experiment to date has been done to formally study its influence. This study investigated the effect of role swapping probability in a modified standard ultimatum game and three “discrete” ultimatum games where proposers were subject to two splits only. The experiment results indicate that with higher role swapping probability, proposers will increase the offer amount and recipients will also demand more, which implies fairer outcomes for both sides.